Fundamentals of Pneumatics and Hydraulics - Salam, Md. Abdus; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book covers the basics of DC circuits, AC circuits, three-phase power to understand the basics and controls of electro-hydraulics and electro-pneumatics. This book covers detailed knowledge on the fluid power properties, Bernoulli$1 (Bs equation, Torricelli$1 (Bs theorem, viscosity, viscosity index, hydraulic pumps, hydraulic valves, hydraulic motors, pressure control valves, pneumatic systems, pneumatic cylinders, different types of gas laws, valve actuation, relay, magnetic contactor, different types of switches, logic gates, electro-pneumatic control circuits with different options and introduction to PLC. In addition, the detailed technique of Automation Studio software, different types of simulation circuits with hydraulics, pneumatics and electro-pneumatic are included. This book will be an excellent textbook for electromechanical, robotics, mechatronics, electrical control and mechanical students as well as for the professional who practices fluid power systems.s
1. Fundamental Electrical Terms -- 2. Analysis of Electrical Power -- 3. Fluid Power Properties -- 4. Hydraulic Pumps -- 5. Hydraulic Directional Valves -- 6. Hydraulic Motors -- 7. Hydraulic Cylinders -- 8. Hydraulic Pressure Control Devices -- 9. Basics of Pneumatic -- 10. Pneumatic System Components -- 11. Electrical Devices and Control of Cylinders -- Index.
Keywords: Power electronics; Electric power production; Hydraulic engineering; Electronic circuits; Power Electronics; Mechanical Power Engineering; Hydraulic Engineering; Electrical Power Engineering; Electronic Circuits and Systems; Electric circuits; Hydraulic machinery; Pneumatic machinery